2021
DOI: 10.1016/j.jag.2021.102421
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown induced night-time light dynamics during the COVID-19 epidemic in global megacities

Abstract: The lockdown of cities to against the COVID-19 epidemic directly decreases urban socioeconomic activities. Remotely sensed night-time light (NTL) provides a macro perspective to capture these variations. Here, taking 20 global megacities as examples, we adopted the NASA’s Black Marble NTL data with a daily resolution to investigate their spatio-temporal changes. We collected daily NTL products for four weeks (one month) before and after the date of lockdown in each city, which were then summarized as weekly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 48 publications
(47 reference statements)
0
47
0
Order By: Relevance
“…Unfortunately, there are not enough studies that have investigated the reduction of anthropogenic light pollution (ALP) to confirm how this has favourably affected ecosystems. While there are some studies that found a decrease [ 108 , 109 , 110 ], there are also studies that have identified an overall increase in ALP [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are not enough studies that have investigated the reduction of anthropogenic light pollution (ALP) to confirm how this has favourably affected ecosystems. While there are some studies that found a decrease [ 108 , 109 , 110 ], there are also studies that have identified an overall increase in ALP [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…To understand changes in energy consumption in response to COVID-19 in each city, we analyse NTL satellite imagery, a well-established proxy for urban energy consumption 26 . In response to COVID-19, NTL imagery has been used to understand the initial impact on the US electricity sector 1 , changes in CO2 emissions nationally 9 , and changes in economic activity in the core of global megacities 27 .…”
Section: Using Ntl Satellite Imagery To Analyse Urban Energy Consumptionmentioning
confidence: 99%
“…Examination of the relationship between population density and NTL intensity (Figure 4) provides insight into the intra-urban distribution of energy consumption in response to COVID-19. Much attention has been paid to the risk of infection in dense urban centres 27,33 , particularly during the early stages of the outbreak. This is evident in cities in which NTL intensity declined 2/16 in densely populated areas (e.g.…”
Section: Shifting Spatial Patterns Of Intra-urban Energy Consumption During Covid-19mentioning
confidence: 99%
“…Xu et al [41] analyzed the lockdown due to COVID-19 in 20 global megacities using nighttime satellite sensor data and found an overall decrease in the NTL brightness with different percentages after the lockdown. Moreover, Asian cities were most affected by the COVID-19 pandemic compared with cities in Europe, Africa, North America and South America [41].…”
Section: Introductionmentioning
confidence: 99%